Twisted Acoustics: Metasurface‐Enabled Multiplexing and Demultiplexing - Jiang, Xue; Liang, Bin; Cheng, Jian‐Chun; Qiu, Cheng‐Wei (Advanced materials (Weinheim), 2018)
Metasurfaces are used to enable acoustic orbital angular momentum (a‐OAM)‐based multiplexing in real‐time, postprocess‐free, and sensor‐scanning‐free fashions to improve the bandwidth of acoustic communication, with intrinsic compatibility and expandability to cooperate with other multiplexing schemes. The metasurface‐based communication relying on encoding information onto twisted beams is numerically and experimentally demonstrated by realizing real‐time picture transfer, which differs from existing static data transfer by encoding data onto OAM states. With the advantages of real‐time transmission, passive and instantaneous data decoding, vanishingly low loss, compact size, and high transmitting accuracy, the study of a‐OAM‐based information transfer with metasurfaces offers new route to boost the capacity of acoustic communication and great potential to profoundly advance relevant fields. Acoustic communication is pivotal in applications such as ocean exploration, while its bandwidth is hitting the ceiling. Twisted acoustics for real‐time information transfer is theoretically proposed and experimentally demonstrated in a passive, postprocess‐free, and sensor scanning‐free fashion with metasurfaces and a single transducer. The study helps to boost the capacity of acoustic communication and advance relevant fields.